Pengaruh Ketersediaan Sumber Belajar di Perpustakaan Sekolah terhadap Motivasi Belajar Siswa pada Mata Pelajaran IPS Terpadu Kelas VIII SMP Negeri 8 Gorontalo (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
The purpose of this study is to analyze the influence of the availability of learning resources in school libraries on student learning motivation in the Integrated Social Sciences (IPS) class VIII subject at SMP Negeri 8 Gorontalo. This research specifically aims to identify the level of availability of learning resources in libraries, such as textbooks, supplementary references, digital media, and other learning support facilities and measure the level of students' learning motivation. This research uses a quantitative approach. The primary data are obtained by distributing questionnaires to SMP Negeri 8 Gorontalo students. The sample size is 30 respondents, and the data analysis techniques use simple linear regression. The results showed that the availability of learning resources in the school library positively and significantly influenced learning motivation. Regression analysis shows a determination of 0.278, which indicates that 27.8% of the variation in learning motivation is explained by the availability of learning resources in the school library. This shows a positive relationship between the availability of learning resources in the school library and learning motivation, where the better the availability of learning resources in the library, the more the student’s learning motivation increases.